Neurobiological intersections of stress and substance use disorders - Juliano, Vitor Augusto Laurino; Albernaz-Mariano, Kairo Alan; Covre, Luiza Helena Halas; Jucá, Paloma Marinho; Pereira, Robbert Mota; Shigeo-de-Almeida, Amadeu; Sampaio, Lucas Luzia; Duque, Erica de Almeida; Munhoz, Carolina Demarchi (Frontiers in Neuroscience, 2025)
Substance use has been intertwined with human history for millennia. Throughout the ages, people have consumed various substances for medicinal, spiritual, and recreational reasons, although occasional use differs significantly from substance use disorders (SUDs). Exposure to lifetime stressors constitutes a significant risk factor for both psychiatric disorders and SUD development and relapse. Indeed, hypothalamic–pituitary–adrenal (HPA) axis modulation, alterations in neuroanatomical and neurotransmitter systems, as well as neuroinflammation are common features of stress-related mood disorders and SUDs. In this mini-review, we will explore how stress exposure influences the SUDs' neurobiological basis on different scales—from large neural circuitries to specific molecular mechanisms—and discuss novel targets for potential treatments.